Operando spectroelectrochemistry of bulk-exfoliated 2D SnS2 for anodes within alkali metal ion batteries reveals unusual tin (III) states - Radtke, Mariusz; Hess, Christian (Frontiers in Chemistry, 2022)
In this study we report an affordable synthesis and preparation of an electrochemically exfoliated few-layer 2-dimensional (2D) SnS2 anode material of high cycling durability and demonstrate its performance on the example of alkali metal batteries. The metalation mechanism consists of highly unusual and previously only speculated Sn (III)-state grasped by operando Raman spectroelectrochemistry aided by symmetry analysis. The prepared 2D material flakes were characterized by high resolution transmission electron microscopy, X-ray photoelectron and Raman spectroscopies. The operando Raman spectroelectrochemistry was chosen as a dedicated tool for the investigation of alkali-metal-ion intercalation (Li, Na, K), whereby the distortion of the A1g Raman active mode (out-of-plane S-Sn-S vibration) during battery charging exhibited a substantial dependence on the electrochemically applied potential. As a result of the structural dynamics a considerable Raman red-shift of 17.6 cm−1 was observed during metalation. Linewidth changes were used to evaluate the expansion caused by metalation, which in case of sodium and potassium were found to be minimal compared to lithium. Based on the spectroscopic and electrochemical results, a mechanism for the de-/intercalation of lithium, sodium and potassium is proposed which includes alloying in few-layer 2D SnS2 materials and the generation of point-defects.